Integrated Socio-Entrepreneurship in Cultural Space: Analysis and Validation Semester Learning Plan - Rahmattullah, Rahmattullah; Sariakin, Sariakin; Akmaluddin, Akmaluddin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to analyze and validate the semester learning plan for entrepreneurship courses with spatial-cultural integration based on PJBL. This research was conducted at the PGSD study program at UBBG, Banda Aceh. The research method is research and development. The instrument used is the RPS of lecturers. Some experts validate the RPS, material experts, linguists, and media experts before it is used in instruction. The observation stage follows the rules: define, design, develop, and disseminate. Based on the results of the study showed that the validity level of the PJBL-based Spatial Integrated Entrepreneurship course was valid; (1) Instructions in the Semester Learning Plan affect it easier for lecturers to convey the purpose of various activities to students, (2) The learning method used is by the material presented, and (3) The Semester Learning Plan can be one of the data for the evaluation of the learning process. This means the PJBL-based spatial-cultural integrated Semester Learning Plan for entrepreneurship courses can already be applied. This study recommends that the designed semester learning plan must be adapted to the learning method used.